The Effect of Operational Complexity, Operating Cash Flow, and Time Interest on Earnings After Tax (E-Jurnal Akuntansi, 2026)
Operational complexity is a factor that can affect the efficiency of production activities and cost structure. The cash flow operating variable describes a company's ability to generate operational cash flow, while time interest earned reflects the company's capacity to meet interest expenses. The quantitative research method uses panel data regression analysis of the annual financial statements of sample companies. The results show that company operational complexity has no significant effect on earnings after tax. Cash flow operating has a significant positive effect on earnings after tax. Time interest earned has a significant positive effect on earnings after tax. These findings provide implications for understanding internal factors that influence financial performance in sectors with high volatility.
Keywords: Company Operational Complexity; Cash Flow Operating; Time Interest Earned; Earning After Tax